2022
DOI: 10.3390/en15217891
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Hybrid CO2 Low Salinity Water-Alternating-Gas Injection and Investigation on Hysteresis Effect

Abstract: Low salinity water injection (LSWI) is considered to be more cost-effective and has less environmental impacts over conventional chemical Enhanced Oil Recovery (EOR) methods. CO2 Water-Alternating-Gas (WAG) injection is also a leading EOR flooding process. The hybrid EOR method, CO2 low salinity (LS) WAG injection, which incorporates low salinity water into CO2 WAG injection, is potentially beneficial in terms of optimizing oil recovery and decreasing operational costs. Experimental and simulation studies reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…For 9 long-core samples in the low-permeability reservoir, 9 cases of displacement experiments were designed to simulate the flooding effects of 3 different flooding methods, namely, continuous gas flooding, WAG flooding with a fixed water-gas ratio, and WAG flooding with a dynamic water-gas ratio, after elastic development, water flooding, and gas flooding. Based on the results of previous research [21][22][23][24][25], the water-gas ratio values of WAG flooding and the dynamic water-gas ratio order were designed. The specific design cases of the displacement experiment are shown in Table 3.…”
Section: Experimental Casesmentioning
confidence: 99%
“…For 9 long-core samples in the low-permeability reservoir, 9 cases of displacement experiments were designed to simulate the flooding effects of 3 different flooding methods, namely, continuous gas flooding, WAG flooding with a fixed water-gas ratio, and WAG flooding with a dynamic water-gas ratio, after elastic development, water flooding, and gas flooding. Based on the results of previous research [21][22][23][24][25], the water-gas ratio values of WAG flooding and the dynamic water-gas ratio order were designed. The specific design cases of the displacement experiment are shown in Table 3.…”
Section: Experimental Casesmentioning
confidence: 99%
“…Consequently, during the subsequent injection of CO 2 , the interplay between the subsurface water and CO 2 gives rise to a CO 2 /water composite fluid. Besides, recent studies have reported positive results using the CO 2 /water composite system for enhanced recovery, and water alternating gas (WAG) is recognized as one efficient injection scheme in some reported field operations. Thus, a comprehensive understanding of the CO 2 /water composite system holds paramount importance in elucidating the mechanisms that underpin the enhanced recovery efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate reservoirs pose unique challenges for EOR due to their intricate pore structures and variable wettability. To address these challenges and mitigate environmental impacts, the application of flue gas and CO 2 injection in WAG and low salinity WAG (LSWAG) techniques has gained attention. , Low salinity water injection (LSWI) is considered a cost-effective and environmentally friendly option compared to conventional chemical EOR methods . WAG injection, which involves the simultaneous CO 2 injection and low salinity water in a hybrid approach known as the CO 2 -LSWAG injection, shows promise in enhancing oil recovery and reducing operational costs.…”
Section: Introductionmentioning
confidence: 99%